2022
DOI: 10.1039/d1tb02352g
|View full text |Cite
|
Sign up to set email alerts
|

[12]aneN3-Conjugated AIEgens with two-photon imaging properties for synergistic gene/photodynamic therapy in vitro and in vivo

Abstract: Six amphiphiles (TTC-L-M-1/2/3/4/5/6), each consisting of hydrophilic macrocyclic polyamine triazole-[12]aneN3 (M) and hydrophobic photosensitizer tetraphenylethenethiophene modified cyanoacrylate (TTC) moiety linked with alkyl chains (L), have been designed and synthesized for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…2C). 22,23 These results suggested that the excellent nucleic acid condensation capability of CNN1-D–CNN3-D was suitable for efficient gene delivery as non-viral gene vector.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…2C). 22,23 These results suggested that the excellent nucleic acid condensation capability of CNN1-D–CNN3-D was suitable for efficient gene delivery as non-viral gene vector.…”
Section: Resultsmentioning
confidence: 92%
“…18,19 We have developed a series of macrocyclic polyamine [12]aneN 3 -derived functional non-viral gene vectors and demonstrated their performance in improving the gene transfection efficiency. [20][21][22][23][24][25] However, cancer therapy based on one single strategy is not always effective, combining multiple therapeutic strategies with synergistic effects may be a promising approach for cancer treatment. 26 Recently, there have been notable advances in cancer therapy through the co-delivery of anticancer drugs and genes, which have achieved synergistic therapeutic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Several different combination therapies have shown excellent anti-cervical cancer efficacy, among which gene therapy (GT)/PDT is widely used. TTC-L-M-4/DOPE was prepared by Liu and Yang et al, and used to transfer siRNA (p53) with good results, indicating that gene silencing effect was better than Lipo2000 [ 123 ]. Meanwhile, TTC-L-M-4 had the ability to effectually produce ROS under light irradiation.…”
Section: Aie-pss For Different Cancers Treatmentmentioning
confidence: 99%
“…Previous reports proved that the p53-mediated pathways can suppress the elimination of intracellular ROS and lipid hydroperoxides. , Meanwhile, ROS may enhance the post-translational modification of p53 and promote p53 protein stabilization and activation . Thus, the synergism between the p53 gene and PDT is a promising strategy for tumor therapy. In particular, combination treatment of p53 and KillerRed by simultaneous codelivery of their respective reporter genes might be advantageous because such a method avoids the heterogeneity between the delivery cargos.…”
Section: Introductionmentioning
confidence: 99%